Reverse genetic analyses of TERMINAL EAR-like RNA-binding protein genes in Arabidopsis thaliana (L.) Heynh. : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Molecular Genetics at Massey University, Palmerston North, New Zealand - Lambie, Suzanne Claire (Massey University, 2008)
In maize, a loss-of-function mutation in a MEI2-like gene, terminal ear1 (te1), leads to morphological defects able to be traced back to the shoot apical meristem. One MEI2-like gene has been identified in maize, while six have been identified in rice and nine in Arabidopsis thaliana. In this thesis, a programme of reverse genetic analysis has been designed to investigate if Arabidopsis genes most closely aligned in parsimony trees with TE1, TERMINAL EAR-LIKE 1 (TEL1), TERMINAL EAR-LIKE 2 (TEL2), perform the same function as TE1. The expression pattern of TEL1 and TEL2 genes is restricted to the Shoot Apical Meristem (SAM) and the Root Apical Meristem (RAM) suggesting these genes are important in meristem maintenance or function. Results of the molecular genetic analysis of TEL genes in Arabidopsis support models in which these genes help maintain cells in a pluripotent state. For the first part of the thesis, analysis of lines carrying single knockouts of TEL1 and TEL2 and double knockout lines reveals a slightly accelerated rate of organogenesis, consistent with these genes normally acting to inhibit terminal differentiation pathways. Plants grown on medium containing gibberellic acid and sucrose, at higher than normal concentrations, present a further accelerated rate of organogenesis. As the second part of the thesis, in situ and promoter/reporter GUS fusion analyses indicate TEL1 is preferentially expressed in both the root and shoot apical meristems. Deletion analysis using GFP reporter constructs show that 5' sequences are sufficient to drive quiescent centre (QC) expression in the root while additional sequences are required for central zone (CZ) expression in the SAM. Physiological studies indicate expression of TEL1 in the root is sensitive to the hormones, auxin, gibberellic acid and zeatin, when added at physiological concentrations. To confirm the auxin effect, GFP expression is no longer visible after 12 hours of exposure to auxin transport inhibitors in plants containing GFP under the control of the TEL1 promoter, suggesting, in common with other QC markers, that TEL expression is sensitive to auxin levels. Analysis of mutant plants with altered root patterning suggests QC specific expression of TEL1 requires early acting genes, such as PLETHORA 1 and 2, but does not depend on later acting genes such as SCARECROW or SHORTROOT.
Keywords: Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression